Retrospective Study of Magnetic Resonance Imaging (MRI) Findings in Pott’s Spine - Sharma, Bishwanath; Panta, Om Biju; Thapa, Bikash Raj; Thapa, Prakash; Khadka, Tirthendra (Nepalese Journal of Radiology, 2021)
Introduction: Skeletal tuberculosis accounts for approximately two percent of all infected tuberculosis (TB). Magnetic resonance imaging (MRI) due to its inherent soft tissue contrast is a very good tool to diagnose the condition and look for its extent and deformities. This study aims to study the MRI findings in a patient with diagnosed case of spinal tuberculosis. Methods: The study was carried out in a referral diagnostic imaging center in western Nepal. All MRI studies of the spine performed in a patient with diagnosed spinal tuberculosis during the study period were included in the study. Patients lacking microbiological or pathological diagnoses of spinal tuberculosis were excluded from the study. Results: A total of 70 patients were included in the study. The mean age of the patients was 45.6 ± 16.8 years. All patients in the study had a spondylodiscitis pattern of involvement. Single intervertebral disc and adjacent vertebrae were involved in 85.7% and multiple contiguous vertebrae and IV discs were involved in 14.3% of cases. Gibbus deformity was seen in 17.1% of cases. Pre/paravertebral and Epidural collections were seen in 95.7% and 72.9% of patients respectively, whereas psoas abscess was seen in 28.6% of patients. Cord compression with myelopathy was seen in 8.6% of patients. Involvement of posterior elements was seen in 27.1% of patients. Conclusion: MRI is an excellent tool to see the extent, deformity, and abscess in spinal tuberculosis. Most patients with tuberculosis present late with collections and deformities.